Exercise-induced traumatic muscle injuries with active bleeding successfully treated by embolization: three case reports - Yoonjung Heo; Hye Lim Kang; Dong Hun Kim (Journal of Trauma and Injury)
Muscle injuries caused by indirect trauma during exercise are common. Most of these injuries can be managed conservatively; however, further treatment is required in extreme cases. Although transcatheter arterial embolization is a possible treatment modality, its role in traumatic muscle injuries remains unclear. In this case series, we present three cases of exercise-induced muscle hemorrhage treated by transcatheter arterial embolization with successful outcomes. The damaged muscles were the rectus abdominis, adductor longus, and iliopsoas, and the vascular injuries were accessed via the femoral artery during the procedures.